ELECTRONIC COURT SEBAGAI ADMINISTRASI HUKUM YANG BAIK (GOOD JUCIAL GOVERNANCE) DI PENGADILAN INDONESIA - Rohadi, Rohadi; Wahid, Abdul; Sumartini, Siti (Jurnal De Jure Muhammadiyah Cirebon, 2023)
The creation of this e-court is a step towards modernizing case management and the judicial process to overcome obstacles in the judicial process as well as an effort to create an open, efficient and effective judiciary. Electronic courts are also expected to be able to apply the principle of simple, fast and affordable justice, which if properly implemented will provide convenience for people seeking justice. One of the principles used in litigation is the principle of simplicity, speed and cheapness. This principle certainly aims so that in any case the investigation process can be carried out quickly, without complicated processes and low costs or borne by interested parties, the presence of an electronic court indicates an effort by the court to provide easy access. to the public and the right seeker. The formulation of the problem of this research is whether electronic service (E-Court) in courts in Indonesia is good judicial governance?. The method in this study uses normative legal research. The results of the discussion are that the existence of an e-court is a special reference to the aspirations of the Supreme Court, but in conventional dispute resolution it can be said that it can realize the principles of simple, fast and cheap justice, but decisions still exist. e-court is a step to maximize the principle of simple, fast and low-level justice in the Indonesian legal system in the judicial environment. The implementation of the E-court system related to the transparency of policy implementation related to pending case fees is one of the impacts on the legal system implemented by other countries. However, even in the E-court system, case fees are still paid through the electronic payment function. Then with the existence of an e-court, the intensity of face-to-face meetings with users of legal services will decrease so that extortion will also decrease. Keywords: E-Court, governance, justice.